Treatment for social media addiction with hypnotic-oriented counseling - Gian Sugiana Sugara; Rikza Fadhilah (Discover Psychology, 2024)
Abstract Background Research has identified social media addiction as a new and often unrecognized clinical disorder that impacts users' ability to control social media use which can lead to relational, work, and social problems. Adolescent who experiences addiction to social media will be very dependent and willing to spend a long time accessing social media so that they experience addiction to social media. This paper reports the findings of a study that used an A-B-A single-case research design to investigate the effect of hypnotherapy to reduce social media addiction in adolescents. Participants consisted of two high school students (N = 2) who had social media addiction behavior in the severe category. Hypnotic-oriented counseling interventions in reducing social media addiction was provided in 5 sessions. Treatment focused on enhancing motivation, emotional release, conflict resolution and empowerment using direct suggestion, parts therapy, circle of excellence technique and anchor. Participants completed the Social Media Addiction Scale for Adolescent. Data was collected before, during, and after the hypnotic-oriented counseling intervention. Result Students who took part in hypnosis-oriented counseling sessions experienced a significant reduction in social media addiction symptoms during and after the intervention. They report becoming increasingly able to manage social media use healthily. Conclusion Hypnotic-oriented counseling intervention was effective in reducing social media addiction symptoms in students.